The Concept of “Original Common Possession” in Kant’s Doctrine of Property - Tomassini, Fiorella (Anales del Seminario de Historia de la Filosofía, 2015)
The first paragraphs of the section “Private Right” (§§ 1-17) of Kant’s Theory of Right include the set of systematic elements concerning the justification of property rights. The main purpose of this paper is to analyze the systematic function of the “original common possession” in the Kantian doctrine of property, with special attention to the novel sense that this concept, which belonged to the natural law tradition, acquires when Kant reformulates it as a “practical rational concept which contains a priori the principle in accordance with which alone people can use a place on the earth in accordance with principles of right” (RL, 262).
Keywords: Kant; Natural Law; Original Common Possession; Property